Основные направления стимулирования интеллектуального труда работников промышленных предприятий - Брюховецкий, Я.С. (Стратегія і механізми регулювання промислового розвитку, 2013)
Рассмотрена сущность интеллектуального труда на уровне предприятий. Определены принципы и факторы формирования систем стимулирования интеллектуального труда на предприятиях, которые должны учитывать как внутрипроизводственные, так и внешние факторы. Даны предложения поповышению эффективности систем стимулирования работников интеллектуального труда на уровне промышленного предприятия. Розглянуто сутність інтелектуальної праці на рівні підприємств. Визначено принципи і фактори формування систем стимулювання інтелектуальної праці на підприємствах, які мають ураховувати як внутрішньовиробничі, так і зовнішні фактори. Надано пропозиції щодо підвищення ефективності систем стимулювання працівників інтелектуальної праці на рівні промислового підприємства. The essence of the intellectual labour at the level of enterprise is viewed. The principles and factors of incentive systems of intellectual labor in enterprises that must take into account both internal and external factors are defined. It is offered to develop the system of labor stimulation taking into account the external factors for the enterprises. The external factors of stimulating intellectual work on the enterprise are denoted: the level of education in the country, the state of science, including the economic, political and economic stability of the country, the region, the spirituality of society, the welfare of society, the state of the labor legislation, labor payment and responsibility for observance of laws, average wages in related enterprises, businesses rivals, the level of innovation activity of the national industry. The proposals are given to improve the efficiency of stimulating intellectual workers at the level of industrial enterprise.